Optimalisasi E-Commerce dalam Meningkatkan Promosi UMKM Produk Lokal di Sumatera Barat - Effendi, Chantika; Annas, Firdaus; Maulida, Mia (JOVISHE : Journal of Visionary Sharia Economy, 2023)
This study aims to design or develop an OpenCart-based e-commerce platform to support the promotion and marketing of local products in South Solok. So far, promotions have been carried out manually through direct visits to the location or limited to social media such as WhatsApp or Instagram and so on, so that the marketing reach carried out in this way can be said to be less than optimal or effective. Conditions in South Solok should have sites to record MSME products in South Solok in order to increase competitiveness, income, and welfare of business actors. This study also uses the Research and Development (R&D) method with the PPE model with stages including Planning, Production and evaluation. The results of this study indicate that the OpenChart-based e-commerce platform provides various features such as a digital product catalog, an online payment system and integration with social media that can facilitate the promotion and sales process. These findings prove that the use of e-commerce technology can increase market reach, competitiveness, and operational efficiency of local business actors. By using a complete implementation, this platform is expected to be an innovative solution to encourage the digitalization of small and medium enterprises (SMEs) in South Solok.